“The Ending Has Not Yet Been Written”: How Myst, S., and Other Transmedia Creations Pay Tribute to the Analog in a Digital World - Bock, Chelsea (Loading, 2025)
With the arrival of new media comes the age-old anxiety that more traditional media – namely tangible forms like the print book – will be displaced, abandoned, or forgotten entirely. However, the book continues to be incorporated into sculptures that surround libraries and clothing and tote bags that we purchase, signifying that the traditional codex holds a lasting place in our hearts. This paper argues that newer forms of media can function as outlets for our love of physical manuscripts and can renew our infatuation with them rather than threaten to replace them. Digital media like Rand and Robyn Miller’s 1993 computer game Myst, as well as transmedia like J.J. Abrams’ and Doug Dorst’s digitally-supplemented novel S. use immersive techniques to recreate the feeling of “losing ourselves” in a good book, intensifying a desire to explore and discover in the physical world and the virtual world alike. Moreover, this paper utilizes Jay David Botler’s and Richard Grusin’s theory of remediation to suggest that transmedia has the potential to inform new engagement with the physical world, as is evident in trends like escape rooms and geocaching.